Invasive pneumococcal disease in Spain 2022 (Boletín Epidemiológico Semanal, 2023)
Introduction: The aim of the study was to describe invasive pneumococcal disease (IPD) epidemiology in Spain during 2022 and its comparison to previous years.Method: Descriptive epidemiological analysis of cases of IPD reported to the National Epidemiological Surveillance Network (RENAVE). The variables analysed were: sex, age, date of symptom onset, place of residence, death and serotype of the Streptoccus pneumoniae.Results: A total of 3,135 cases of IPDs were reported, with an incidence rate per 100,000 population (IR) of 6.58. The incidence was highest in children under 1 year of age (IR of 24.89) and in the 1 - 4 year age group (IR of 18.42). Serotypes 8 and 3 caused 42.7% of the IPDs in which the serotype was reported. In the under 1 and 1 - 4 year age groups, 29.8% and 34.4% of IPD were caused by PCV13 serotypes, respectively (47.1% and 78.8%, respectively, were caused by serotype 3). In the age group 65 years and older, 70.2% of IPDs were caused by serotypes included in PPV23 . 36.8% and 64.8% of IPD were caused by serotypes included in PCV15 and PCV20, respectively.Conclusions: IR increased in all age groups but was lower than pre-pandemic TI except in age groups 1-4 and 5-14 where IR was higher. Serotypes 8 and 3 were responsible for 42.7% of IPDs with known serotype.
Keywords: Invasive pneumococcal disease; Pneumococcal vaccines; Spain; 2022; Epidemiological analysis; RENAVE